Rayleigh lidar studies of the Arctic middle atmosphere - Cutler, Laura Jeanette (2000)
Thesis (M.S.) University of Alaska Fairbanks, 2000 Rayleigh lidar allows us to measure density and temperature structure of the atmosphere at heights from approximately 35 to 80 kilometers. A Rayleigh lidar was installed at Poker Flat Research Range in November of 1997 and has been operated routinely since. This thesis presents an engineering analysis of the lidar system performance and a scientific analysis of the data obtained. The engineering analysis considers the receiver and transmitter alignment of the lidar system and the signal quality of the lidar data. The scientific analysis considers the retrieval of density and temperature profiles under a range of geophysical conditions. This study uses a three-year data set that includes 38 nights of data.